1992
DOI: 10.1038/358031a0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the disorder in network-modified silicate glasses

Abstract: Local order in silicate glasses has been observed by many experimental techniques to be similar to that in crystalline materials. Details of the intermediate-range order are more elusive, but essential for understanding the lack of long-range symmetry in glasses and the effect of composition on glass structure. Two-dimensional 17O dynamic-angle-spinning nuclear magnetic resonance experiments reveal intermediate-range order in the distribution of inter-tetrahedral (Si-O-Si) bond angles and a high degree of orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
279
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(311 citation statements)
references
References 26 publications
28
279
3
1
Order By: Relevance
“…At ordinary density, the angle shows a broad distribution between 120 • and 180 • and centered at 153 • (see also Fig. 6a), compared to the 142 • experimental value from NMR 45,46 . This difference was also observed by previous simulations, as reviewed in 19 and is consistent with the over estimated value of the Si-Si distance.…”
Section: Bond-angle Distributionsmentioning
confidence: 99%
“…At ordinary density, the angle shows a broad distribution between 120 • and 180 • and centered at 153 • (see also Fig. 6a), compared to the 142 • experimental value from NMR 45,46 . This difference was also observed by previous simulations, as reviewed in 19 and is consistent with the over estimated value of the Si-Si distance.…”
Section: Bond-angle Distributionsmentioning
confidence: 99%
“…A wide distribution of the Si-O-Si angle from ~120° to 180° is consistent with the reported results. 38,39) According to previous studies, 43,48) the introduction of a modifier will cause the decrease of the Si-O-Si angle in the silicate network. The average angle of the Si-O-Si, listed in Table 5, slightly decreases from ~155° to 151° with increasing the V 2 O 3 content, this may be an indication that V 2 O 3 act as a modifier in this tetrahedral network.…”
Section: Local Structure Of the Meltsmentioning
confidence: 99%
“…This can be converted to a distribution function, X(␤), of the secants of all Si-O-Si bond angles, where ␤ = sec ␣. This distribution is then used to calculate V(␣) via Dupree & Pettifer (1984) and Farnan et al (1992) used this method to determine the Si-O-Si bond-angle distribution. The model of Dupree & Pettifer (1984) that gave the best agreement with experiment has a broad, symmetric V(␣) distribution with nearly constant probability over 140-155°, whereas Farnan et al (1992) obtained a V(␣) distribution from ~130 to 180° for glass of K 2 Si 4 O 9 composition, with a maximum at 143° consistent with the data obtained by Mozzi & Warren (1969) for SiO 2 glass.…”
Section: The Sio 4 Tetrahedron (Short-range Order)mentioning
confidence: 99%
“…This distribution is then used to calculate V(␣) via Dupree & Pettifer (1984) and Farnan et al (1992) used this method to determine the Si-O-Si bond-angle distribution. The model of Dupree & Pettifer (1984) that gave the best agreement with experiment has a broad, symmetric V(␣) distribution with nearly constant probability over 140-155°, whereas Farnan et al (1992) obtained a V(␣) distribution from ~130 to 180° for glass of K 2 Si 4 O 9 composition, with a maximum at 143° consistent with the data obtained by Mozzi & Warren (1969) for SiO 2 glass. However, Mauri et al (2000) showed that the average Si-O-Si angle calculated from NMR spectra is not consistent with the distribution of Mozzi & Warren (1969), but closer to a mean of 151°.…”
Section: The Sio 4 Tetrahedron (Short-range Order)mentioning
confidence: 99%